Defence and discovery Canada's military space program, 1945-74 - Godefroy, Andrew B., 1972- (Studies in Canadian military history., 2011)
The Cold War space race between the United States and the Soviet Union is well documented, but few are aware of Canada's early activities in this important arena of global power. Defence and Discovery represents the first comprehensive investigation into the origins, development, and impact of Canada's space program from 1945 to 1974. Meticulously researched, it demonstrates the central role of the military in Canada's early space research, illuminating a significant yet understudied period in Canada's growth as a nation.